A NEW SPECIES OF CYPRINID FISH: Puntius bunau FROM THE SETURAN BASIN OF INDONESIAN BORNEO - Ike Rachmatika (BRIN Publishing (Penerbit BRIN), 2004)
Puntius bunau, neto species from the Seturan Watershed, Bulungan, East Kalimantan, Indonesia is distinguished from its congellers by the combination of the following characters: a black triangular bar all the side of the body under the dorsal fill, black spots behind the opercle, a black bar all the edge of the anal fill, 22-23 lateral line scales, predorsal profile convex, and eye diameter 21.28-29.73% of head length.